Analysis of Combustion Temperature on Specific Fuel Consumption (SFC) of Diesel Engines Using B30 Fuel in the Long Term Performance - Erwan Adi Saputro; Wiliandi Saputro (Future Science, 2022)
The world's energy keeps continuing to increase, meanwhile, the fossil energy used creates emissions problems and long-term dependence. Therefore, it is necessary to diversify energy to new and renewable energy. Especially to replace fossil energy whose availability is reducing. One alternative energy that has the potential to continue to be developed is biodiesel. Indonesia is currently one of the largest palm oil-producing countries in the world with a total production of 40 million tons by 2020. Biodiesel can be used directly without having to modify the combustion chamber of a diesel engine. However, the use of biodiesel, especially B30 (30% biodiesel + 70% diesel mixture) which is currently used in Indonesia, must receive special attention for the effects if applied to diesel engines in the long term. Therefore, the purpose of this study is to analyze the use of B30 on the performance of the diesel engine produced with a test time of 200 hours of operation. This study uses an experimental method, with a loading using a 4000 Watt halogen lamp. Engine rotational speed is kept constant at 2200 RPM and measurement of fuel consumption per unit time using a burette. Fuel consumption was measured using a manual technique with a 20 ml capacity burette, while the time the engine spent fuel was measured using a stopwatch. Based on the test results, the average power and torque values ??produced by the B30 engine are 4.45 kW and 12.54 N.m. Meanwhile, the value of specific fuel consumption and average thermal efficiency produced is 0.28 kg/kW.hour and 29.43%. Performance changes in diesel engines can be influenced by several factors including the calorific value of the fuel and the viscosity value of the B30 fuel used.